2010
DOI: 10.1007/s10682-010-9382-5
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of facultative parthenogenesis in the ant Platythyrea punctata

Abstract: Thelytokous parthenogenesis, the production of diploid female offspring from unfertilized eggs, can be caused by several cytological mechanisms, which have a different impact on the genetic variation on the offspring. The ponerine ant Platythyrea punctata is widely distributed throughout the Caribbean Islands and Central America and exhibits facultative parthenogenesis. Workers in many field colonies from the Caribbean Islands have identical multilocus genotypes and are thus probably clonal, but the occurrence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…Alternatively, it is possible that M. smithii queens reproduce via meiotic parthenogenesis (automixis) with central fusion, a cytogenetic mechanism characterized by potentially very low recombination rates, depending on the locus's distance to the centromere, as indicated by genotype pairs that differ only at a single locus. Automixis with central fusion has been documented in social Hymenoptera (18,19,26,28,29,51,52), and a recent study of W. auropunctata reported recombination rates as low as 0-2.8% (31). Our current data, however, are insufficient to clearly distinguish between automixis with a low recombination rate and apomixis with rare gene conversion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it is possible that M. smithii queens reproduce via meiotic parthenogenesis (automixis) with central fusion, a cytogenetic mechanism characterized by potentially very low recombination rates, depending on the locus's distance to the centromere, as indicated by genotype pairs that differ only at a single locus. Automixis with central fusion has been documented in social Hymenoptera (18,19,26,28,29,51,52), and a recent study of W. auropunctata reported recombination rates as low as 0-2.8% (31). Our current data, however, are insufficient to clearly distinguish between automixis with a low recombination rate and apomixis with rare gene conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Population-genetic studies of some species revealed a diversity of highly complex genetic systems, including different cytogenetic mechanisms used to produce workers and queens, facultative sexual reproduction, and clonal male lineages (23)(24)(25)(26)(27). Asexual eusocial Hymenoptera produce diploid offspring via meiotic parthenogenesis, or automixis, in which a limited amount of genetic variability is generated through fusion of sister nuclei (28)(29)(30)(31). In contrast, mitotic parthenogenesis, or apomixis, in which offspring are genetic clones of their mothers, has not been demonstrated unambiguously in social insects.…”
mentioning
confidence: 99%
“…However, these authors sampled only eight colonies and the frequency of colonies producing diploid males in their study (0/8) does not differ significantly from that of the present study (7/18; Fisher exact test P=0.15). Production of diploid males due to automictic thelytokous reproduction was reported in two other haplodiploid species: the ant P. punctata (Kellner and Heinze 2011) and the Cape honey bee (Goudie et al 2012). Diploid males in many species might die or be selectively killed by workers at early larval stages as observed for instance in the thelytokous Cape honey bee (Goudie et al 2012).…”
Section: Thelytokous Parthenogenesis Results In Dmp In C Cursormentioning
confidence: 90%
“…In the few social insect species where it has been studied, parthenogenesis is automictic with central fusion (honey bees: Apis mellifera capensis, Verma and Ruttner 1983; ants: Cataglyphis cursor, Pearcy et al 2006; Wasmania auropunctata, Rey et al 2011; Platythyrea punctata, Kellner and Heinze 2011). This mode of parthenogenesis results from the fusion of two of the products of meiosis that were separated during the first meiotic cellular division (Suomalainen et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Co-occurrence of sexual and asexual reproduction is found in various insect species, including parasitoid wasps (Day and Hedlund 1988, Stouthamer et al 1990, Arakaki and Kinjo 1998, Huigens et al 2000, Schneider et al 2002, Copeland et al 2010, ants (Kellner and Heinze 2011), honey bees (Greeff 1996), aphids (Simon et al 2002), cockroaches (Corley and Moore 1999), and thrips (Mound 1992, Nakao and Yabu 1998, Nault et al 2006. Sympatric sexual and asexual populations offer excellent models to evaluate the relative costs and beneÞts of sex.…”
Section: Discussionmentioning
confidence: 99%